In vitro evaluation of antioxidant properties of Moringa oleifera, Centella asiatica, and Nigella sativa: individual and combined effects - Capritasari, Rafiastiana; Setianto, Arif Budi; Akrom; Rais, Ichwan Ridwan; Anwar, Muslih; Sun, Suny (Pharmaciana, 2025)
Oxidative stress, a condition linked to various degenerative diseases, occurs when reactive species build up in the body. These harmful molecules often come by environmental factors like air pollution as well as by unhealthy lifestyle habits. Fortunately, nature gives a defense system: plants produce flavonoids and other phenolic substances that act as natural antioxidants, handling to neutralize reactive species and protecting the body by their damaging effects. The objective of the study was to determine the phytochemical content of extracts of M. oleifera leaf, C. asiatica leaf, and N. sativa Oil and their operation as antioxidants. The study applied both qualitative and quantitative phytochemical tests to measure flavonoid levels in the extracts. Bioactive substances were then identified through GC-MS and LC-HRMS, while antioxidant operation was assessed utilizing the DPPH method. The outcomes were drawn that Moringa oleifera and Centella asiatica extracts contained flavonoids, alkaloids, tannins, saponins, and steroids, while Nigella sativa oil contained terpenoids. Among the three, LC-HRMS screening drawn that Moringa oleifera extract had the highest diversity of flavonoid substances. The outcomes of GC-MS obtained 13 components identified in Nigella sativa oil, one of that was thymoquinone. The antioxidant operation IC50 scores were as follows: 57.943 ± 3.481 µg/mL (M. oleifera), 66.578 ± 1.979 µg/mL (C. asiatica), 56.174 ± 1.604 µg/mL (N. sativa), and 51.128 ± 1.724 µg/mL (polyherbal combination). All the samples demonstrated strong antioxidant operation, and notably, the combination of extracts proved to be more effective than when each to be utilized individually.